THE EFFECT OF FOOD SELF-SUFFICIENCY ON STATE SOVEREIGNTY IN A DEVELOPING COUNTRY: Case study of rice in Senegal - Niane Amadou Toubab (Graduate School of International Studies Ajou University, 2014)
ABSTRACT The thesis considers the interrelationship between neoliberalism, sovereignty and self sufficiency These relationships are discussed in the wider and historical context of food security in African-Chinese relations as these relations are often defined by food resource questions The principle conclusions are that self-sufficiency and domestic production are being undermined by neoliberal policies at the expense of State sovereignty. Whilst neoliberalism is understood to be challenging state sovereignty the paper argues that this relationship and the current research on this relationship obscures, and therefore reinforces, the more fundamental causal factor behind growing food insecurity and future food vulnerability in Senegal as a result of policies that do not attend to issues of self sufficiency which are providing adequate food security to the Senegalese population The future rethinking of this relationship between sovereignty and self sufficiency in an increasingly globalizing world is therefore key not only to rethinking ongoing African-Chinese relations but also attending to domestic implications of economic and social instability in Senegal.
학위논문(석사)--아주대학교 Graduate School of International Studies :국제통상학과,2014. 8